Wilckodontics: Periodontally Accelerated Osteogenic Orthodontics - Tushar Sakal Pathak (New Horizons in Medicine and Medical Research Vol. 2, 2022)
The objective of this article is to highlight the advantages of Wilckodontics in accelerating the local hard and soft tissue remodelling and thereby bring about a decrease in the time taken to complete the orthodontic treatment. The second objective is to minimise or remove the need of orthodontic appliances which can be cumbersome for the patient. Wilckodontics is also known as periodontally accelerated osteogenic orthodontics (PAOO). The periodontium is a dynamic tissue and regulation of its remodeling gives an edge in the traditional orthodontic treatment. The synergistic effort from the periodontic and orthodontic fields in the PAOO technique can shorten the conventional orthodontic treatment time to 3 to 9 months.This technique has roots in orthopedics, dating back to the early 1900s.It was only recently updated to help straighten teeth and correct bites. This page will help you grasp Wilckodontics indications, contraindications, and complexities.